Innovative and sustainable local material in traditional African architecture: Socio cultural dimension (2008)
Local materials are the resources that can be found readily in large quantity at a particular location or area at a certain time. It could also be referred to as materials that can be used to fabricate a finished element. These materials however could be abundant in some area but not available in another. The availability may largely be dependent on geographical location of the area as well as the chemical and physical components of such materials. The paper critically appraises some local material available in south west Nigeria. The investigation revealed such materials as laterite, textile, bamboo, mosaic, mats stones, dye, timber, tusks, snail shell, cow dung, cowries cane and mud. These materials are cheap relative to the imported materials from outside the country. The neglect of these readily available materials should be discouraged. The paper also suggests practical and innovative ways for designers, architects and manufacturers which can serve as an alternative source of material and yet sustainable; and in the long run profitable for all concern. Proper inventory, investments, packaging and modernization can help generate much needed foreign exchange and serve as promotion of the local culture. Close attention must be paid to the sustainable methods and means of using these materials for the good of all. Diagrams, pictures, plates and their application of these materials are also showcased in the paper.